Lubricants based on synthesised emulsifier-stabilizer - Bodachivska, Larysa Yu.; Safronov, Oleg I.; Venger, Iryna O.; Verba, Artem Yu. (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2025)
Hydroxylated fatty acids were synthesized by epoxidation of unsaturated fatty acids of waste food oil followed by hydrolysis by acylglycerol grouping and oxirane rings. The fatty acid aminoamides of the oils were synthesized by epoxidation of used fooding oil, followed by opening of the oxirane cycle and transamidation of acylglycerols with diethanolamine. The use of lithium soaps of hydroxyacids from waste food oil as an emulsifier-stabilizer, which acts as a lubricant thickener, and the introduction of fatty acid aminoamides of oils as an antioxidant additive into the composition of lubricants made it possible to obtain a plastic (lithium) lubricant. The physicochemical properties of lubricant were investigated and their quality indicators were compared with lubricant based on 12-hydroxystearic acid. The developed lithium lubricant is characterized by improved protective and tribological characteristics, increased stability to oxidation and mechanical stress, does not cause corrosion of non-ferrous metals, and is not inferior to lithium lubricant based on an industrial analog of 12-hydroxystearic acid. The lubricant is intended for friction units of machines and mechanisms. The properties of the resulting lubricant make it possible to predict its long service life in components and mechanisms and the prospects for using the components used in lubricant formulations. On the one hand, these studies make it possible to replace imported components for the production of lubricant thickeners, and on the other hand, to solve the problem of utilization of by-products of oil and fat production.